Traditional Chinese Medicine treatment as maintenance therapy in advanced non-small-cell lung cancer: A randomized controlled trial. (February 2016) - Jiang, Yi; Liu, Ling-Shuang; Shen, Li-Ping; Han, Zhi-Fen; Jian, Hong; Liu, Jia-Xiang; Xu, Ling; Li, He-Gen; Tian, Jian-Hui; Mao, Zhu-Jun
Highlights: This RCT compared the effects of TCM maintenance therapy with that of chemotherapy. TCM maintenance therapy had similar effects on TTP and OS compared with chemotherapy. TCM maintenance therapy improved patients' QOL compared with chemotherapy. TCM maintenance therapy had higher 1-year survival rate compared with chemotherapy. TCM maintenance therapy is a promising option for advanced NSCLC patients. Abstract: Objectives: Maintenance therapy for patients with advanced non-small-cell lung cancer (NSCLC) is an increasingly hot topic in the field of clinical NSCLC research. This study aimed to evaluate the effects of Traditional Chinese Medicine (TCM) treatment as maintenance therapy on time to progression (TTP), quality of life (QOL), overall survival (OS) and 1-year survival rate in patients with advanced NSCLC. Methods: This study was conducted as a randomized, controlled, open-label trial. 64 non-progressive patients who responded to initial therapy were randomized 1:1 to the TCM arm (treated with herbal injection (Cinobufacini, 20 ml/d, d1–d10), herbal decoction (d1–d21) and Chinese acupoint application (d1–d21), n = 32) or to the chemotherapy arm (treated with pemetrexed (non-squamous NSCLC, 500 mg/m 2, d1), docetaxel (75 mg/m 2, d1) or gemcitabine (1250 mg/m 2, d1 and d8), n = 32). Each therapy cycle was 21 days. They were repeated until disease progression, unacceptable toxicity, or until the patients requested therapy discontinuation. The primary end point was TTP; the secondary end points were QOL, OS and 1-year survival rate. "Intention-to-treat" analysis included all randomized participants. Results: TCM treatment prolonged median TTP for 0.7 months compared with chemotherapy, but it was not statistically significant (3.0 months vs. 2.3 months, P = 0.114). Median OS time for TCM treatment did not offer a significant advantage over for chemotherapy (21.5 months vs. 18.8 months, P = 0.601). 1-year survival rate of TCM treatment significantly improved than that of chemotherapy (78.1% vs. 53.1%, P = 0.035). TCM treatment can significantly improve QOL when compared to chemotherapy as assessed by EORTC QLQ-C30 and EORTC QLQ-LC13 QOL instruments. Conclusions: TCM maintenance treatment had similar effects on TTP and OS compared with maintenance chemotherapy, but it improved patients' QOL and had higher 1-year survival rate. TCM Maintenance treatment is a promising option for advanced NSCLC patients without progression following first-line chemotherapy.